Tecnologías disruptivas: el reto para las industrias en los ámbitos de inclusión y desarrollo sostenible (2017)
Became apparent the various characteristics of social and economic character that are affected by the inclusion of disruptive technologies in industries, mainly emphasizing the human factor and the interaction with its environment. Aspects such as the migration of the research from the Academy towards the industrial sector resulting in the empowerment of the market services. In addition, we examined the impact that would have increased the research in terms of profitability and the consequences of the implementation of innovative projects that aim to direct industries towards the success, finally establishing a comparison between countries in terms of generation of patents and innovation and determined that there are gaps that establish a level of development based on the technologies that each nation can generate.